Genetic Variation in Acid Ceramidase Predicts Non-completion of an Exercise Intervention - Lewis, Lauren S.; Huffman, Kim M.; Smith, Ira J.; Donahue, Mark P.; Slentz, Cris A.; Houmard, Joseph A.; Hubal, Monica J.; Hoffman, Eric P.; Hauser, Elizabeth R.; Siegler, Ilene C.; Kraus, William E. (Frontiers in Physiology, 2018)
Genetic variation is associated with a number of lifestyle behaviors; it may be associated with adherence and individual responses to exercise training. We tested single nucleotide polymorphisms (SNPs) in the acid ceramidase gene (ASAH1) for association with subject adherence and physiologic benefit with exercise training in two well-characterized randomized, controlled eight-month exercise interventions: STRRIDE I (n=239) and STRRIDE II (n=246). Three ASAH1 non-coding SNPs in a linkage disequilibrium block were associated with non-completion: rs2898458(G/T), rs7508(A/G), and rs3810(A/G) were associated with non-completion in both additive (OR=1.8,1.8,2.0; P<0.05 all) and dominant (OR=2.5,2.6,3.5; P<0.05 all) models; with less skeletal muscle ASAH expression (p<0.01) in a subset (N=60); and poorer training response in cardiorespiratory fitness (peak VO2 change rs3810 r2 =0.29, P=0.04; rs2898458 r2 =0.29, P=0.08; rs7508 r2 =0.28, p=0.09); and similar in direction and magnitude in both independent exploratory and replication studies. Adherence to exercise may be partly biologically and genetically moderated through metabolic regulatory pathways participating in skeletal muscle adaptation to exercise training.